2016
DOI: 10.1099/jgv.0.000347
|View full text |Cite
|
Sign up to set email alerts
|

Age- and strain-dependent differences in the outcome of experimental infections of domestic pigs with wild boar pseudorabies virus isolates

Abstract: Although pseudorabies virus (PRV) has been eradicated in domestic swine in many countries, its presence in wild boars remains a threat for a reintroduction into the currently unprotected swine population. To assess the possible impact of such a reintroduction in a naive herd, an in vivo infection study using two genetically characterized wild boar PRV isolates (BEL24043 and BEL20075) representative for wild boar strains circulating in south-western and central Europe and the virulent NIA3 reference strain was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Many other variations in amino acid residues were observed between the various PRV strains, as for example, at positions 16, 25, 38, or 39. Many of them have also been observed in previous studies conducted in other countries [10,13,35], but these differences in gC did not seem to relate to biological differences in vitro [12]. In vivo, it was demonstrated that two Belgian PRV strains differing from each other by the amino acid at position 18 presented attenuated clinical signs in adult pigs, but only one of them induced a major respiratory and neurological disease in young piglets [36]. Sequencing the partial UL44 gene, which is only a small part of the PRV genome, is not sufficient to assume a possible difference in the pathogenicity of PRV strains.…”
Section: Discussionmentioning
confidence: 62%
“…Many other variations in amino acid residues were observed between the various PRV strains, as for example, at positions 16, 25, 38, or 39. Many of them have also been observed in previous studies conducted in other countries [10,13,35], but these differences in gC did not seem to relate to biological differences in vitro [12]. In vivo, it was demonstrated that two Belgian PRV strains differing from each other by the amino acid at position 18 presented attenuated clinical signs in adult pigs, but only one of them induced a major respiratory and neurological disease in young piglets [36]. Sequencing the partial UL44 gene, which is only a small part of the PRV genome, is not sufficient to assume a possible difference in the pathogenicity of PRV strains.…”
Section: Discussionmentioning
confidence: 62%
“…Phylogenetic analysis of a part of the gC gene, performed in accordance with literature standards (Goldberg et al, 2001;Hahn et al, 2010;Müller et al, 2010), showed that these isolates cluster together with other wild boar isolates from south-western Europe in clade B and can therefore be considered as representative strains (Verpoest et al, 2014). The virulence of two of these wild boar strains, BEL20075 and BEL24043, was tested in vivo in 2-and 15-week-old domestic pigs, and indicated the attenuated nature of these strains in adult pigs (Verpoest et al, 2016). Domestic swine strains were directly obtained from domestic swine that were euthanized after experiencing important clinical symptoms typical for Aujeszky's disease.…”
mentioning
confidence: 63%
“…In this report, we present a study of the pathogenesis and associated cytokine mRNA expression in 2- and 15-week-old domestic pigs after infection with the previously characterized wild boar PRV isolate BEL24043. 7 In addition, we compare and contrast these results to our previous study with the virulent domestic NIA3 strain 8 and from this suggest mechanistic explanations for the age-dependence of infection and the overall reduced virulence of the BEL24043 strain.…”
Section: Introductionmentioning
confidence: 72%
“…While two Belgian wild boar strains were attenuated in adult pigs (BEL24043 and BEL20075), only one induced important respiratory and neurological disease in 2-week-old piglets (BEL24043). 7 Overall, cell biological and molecular explanations for the observed differences in virulence between PRV strains, and particularly wild boar strains, are lacking.…”
Section: Introductionmentioning
confidence: 99%